Penanaman Bibit Mangrove Guna Mengurangi Dampak Lingkungan di Pantai Tirang Semarang - Kundori; Hermawati, Lilin; Mujiarto, Iman; Mahendro, Iwan (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service activity aims to plant mangrove tree seedlings that are expected to be used as pollutant absorbers and prevent seawater abrasion, educational facilities, carbon storage, and coastal tourism. The method used is by conducting lectures and direct practice by planting mangrove tree seedlings. This service activity is carried out in several stages including observation, coordination, execution, and evaluation. Observations were made by coming to Tirang Beach to determine the location for planting mangrove seedlings. tirang beach was chosen due to beach abrasion due to rising seawater and abrasion. The coordination stage is carried out by the community service team together with the Tirang beach manager. The aim is to coordinate so that community service activities can run smoothly and on target. The execution was carried out by planting mangrove tree seedlings on the beach, especially those affected by abrasion. While the evaluation is by looking at the deficiencies that were carried out during community service activities. The activity of planting mangrove trees is beneficial for increasing public awareness of environmental concerns by planting trees and for reducing greenhouse gas emissions so as to reduce impact global warming.